Fabrication of All-Solid-State Lithium-Ion Cells Using Three-Dimensionally Structured Solid Electrolyte Li7La3Zr2O12 Pellets - Shoji, Mao; Munakata, Hirokazu; Kanamura, Kiyoshi (Frontiers in Energy Research, 2016)
All-solid-state lithium-ion batteries using Li+-ion conducting ceramic electrolytes have been focused on as attractive future batteries for electric vehicles and renewable energy conversion systems because high safety can be realized due to non-flammability of ceramic electrolytes. In addition, a higher volumetric energy density than that of current lithium-ion batteries is expected since the all-solid-state lithium-ion batteries can be made in bipolar cell configurations. However, the special ideas and techniques based on ceramic processing are required to construct the electrochemical interface for all-solid-state lithium-ion batteries since the battery development has been done so far based on liquid electrolyte system over 100 years. As one of promising approaches to develop practical all-solid-state batteries, we have been focusing on three-dimensionally (3D) structured cell configurations such as an interdigitated combination of 3D pillars of cathode and anode, which can be realized by using solid electrolyte membranes with hole-array structures. The application of such kinds of 3D structures effectively increases the interface between solid electrode and solid electrolyte per unit volume, lowering the internal resistance of all-solid-state lithium-ion batteries. In this study, Li6.25Al0.25La3Zr2O12 (LLZAl), which is a Al-doped Li7La3Zr2O12 (LLZ) with Li+-ion conductivity of 10–4 S cm–1 at room temperature and high stability against lithium-metal, was used as a solid electrolyte, and its pellets with 700 um depth holes in 700 x 700 um2 area were fabricated to construct 3D-structured all-solid-state batteries with LiCoO2 / LLZAl / lithium-metal configuration. It is expected that the LiCoO2-LLZAl interface is formed by point to point contact even when the LLZAl pellet with 3D hole-array structure is applied. Therefore, the application of mechanically soft Li3BO3 with a low melting point at around 700 °C was also performed as a supporting Li+-ion conductor to improve the LiCoO2-LLZAl interface.